2020
DOI: 10.3390/ijerph17155464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Misophonia and Correlates of Its Symptoms among Inpatients with Depression

Abstract: Misophonia is an underexplored condition that significantly decreases the quality of life of those who suffer from it. It has neurological and physiological correlates and is associated with a variety of psychiatric symptoms; however, a growing body of data suggests that it is a discrete disorder. While comorbid diagnoses among people with misophonia have been a matter of research interest for many years there is no data on the frequency of misophonia among people with psychiatric disorders. This could be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 40 publications
4
35
3
6
Order By: Relevance
“…The total score is obtained by summing the scores for each item, it ranges from 14 to 70. A total score above (or equal to) 61 suggests misophonia diagnosis 18 . Siepsiak et al 18 chose this cut-off by subtracting one standard deviation (SD = 4.3) from the mean total score of misophonics (mean = 65.72).…”
Section: Methodsmentioning
confidence: 99%
“…The total score is obtained by summing the scores for each item, it ranges from 14 to 70. A total score above (or equal to) 61 suggests misophonia diagnosis 18 . Siepsiak et al 18 chose this cut-off by subtracting one standard deviation (SD = 4.3) from the mean total score of misophonics (mean = 65.72).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting finding was that avoidant coping and PPD were not related. The relationship between avoidance and depressive symptoms has been extensively analyzed in both clinical [ 63 , 64 ] and non-clinical samples [ 26 ]. Its study in the context of PPD has been less frequent, but studies appear to indicate modest, yet significant associations between avoidant coping in the mothers and PPD [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total score above (or equal to) 61 suggests misophonia diagnosis 13 . Siepsiak et al 13 chose this cut-off by subtracting one standard deviation (SD = 4.3) from the mean total score of misophonics (mean = 65.72). To verify this cut-off, we performed a Receiver Operating Characteristic (ROC) 14 analysis of data from Siepsiak et al 11 (Supplementary Data "raw_data2.csv") and found that a cut-off of 61 was optimal in separating MisoQuest total scores of controls (n=254) from scores of misophonics (n=61).…”
Section: Online Taskmentioning
confidence: 99%
“…The total score is obtained by summing the scores for each item, it ranges from 14 to 70. A total score above (or equal to) 61 suggests misophonia diagnosis 13 . Siepsiak et al 13 chose this cut-off by subtracting one standard deviation (SD = 4.3) from the mean total score of misophonics (mean = 65.72).…”
Section: Online Taskmentioning
confidence: 99%
See 1 more Smart Citation